2021
DOI: 10.21203/rs.3.rs-79982/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serine Proteases Profiles of Leishmania (Viannia) Braziliensis Clinical Isolates With Distinct Susceptibilities to Antimony

Abstract: Glucantime® (SbV) is the first-line treatment against leishmaniasis in South America. Its effectiveness has been associated with modulation of the parasite detoxification system that, in turn, is related to serine proteases such as subtilisins. In this study, 12 Leishmania (Viannia) braziliensis isolates from patients that presented clinical cure (Responders - R) and relapse or therapeutic failure (Non-responders - NR) were used. The parasites were assessed by in vitro susceptibility to SbIII and SbV, serine p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In fact, the results presented here contribute to reinforce the heterogeneity previously seen for these clinical isolates. (31,32)…”
mentioning
confidence: 99%
“…In fact, the results presented here contribute to reinforce the heterogeneity previously seen for these clinical isolates. (31,32)…”
mentioning
confidence: 99%
“…The heterogeneous composition of parasite populations in Leishmania spp. can be illustrated by phenotypic variations in antimony susceptibility, as observed for L. (V.) braziliensis, Leishmania (V.) guyanensis and Leishmania (L.) amazonensis isolates (Moreira et al ., 1998; Zabala-Peñafiel et al ., 2021), and for Leishmania (L.) donovani isolates which were described as a mixture of subpopulations susceptible and resistant to sodium stibogluconate (Pal et al ., 2001; Bhattacharyya et al ., 2002). Another example for the role of population structure in the environmental adaptive success of the parasites is the study performed with L. (L.) major submitted to in vitro treatment with miltefosine, which indicated that resistance is related to population heterogeneity, with subpopulations that differ in susceptibility phenotypes (Coelho et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%